Discrete Element Method Study on Spreading Behaviour of Non-spherical Polymeric Powder in Powder Bed Fusion with Blade and Roller Spreaders - Sina Zinatlou Ajabshir; Colin Hare; Diego Barletta; Massimo Poletto (Chemical Engineering Transactions)
The properties of the spread powder layer are key in Powder Bed Fusion (PBF) additive manufacturing. Higher packing density and a uniform powder layer are vital for part quality. This study examined the impact of blade-shaped and roller-shaped spreading tools on powder behaviour using the Discrete Element Method (DEM). Switching from a blade to a roller at a spreading speed of 30 mm/s improved the packing fraction by 76% and reduced surface roughness by 16%. The roller-shaped tool produced a more effective initial powder layer with a better packing fraction and a smoother surface finish.